Sexual dysfunction in men seeking infertility treatment: The prevalence and associations - Afsaneh Bakhtiari; Zahra Basirat; Mohammad-Reza Aghajani Mir (Babol University of Medical Sciences, 2015)
Introduction: Infertility is a major stressor in life and can cause disturbances in both sexual and marital relationships. Therefore, the objective of this study was to determine the frequency of sexual dysfunctions among infertile couples, who referred to the infertility center in Babol, Iran, and the identification of the factors associated with these problems. Method: A cross-sectional study was performed on 236 partners of infertile couples. A standard questionnaire named international classification DSM-IV was used to assess the frequency and the type of sexual dysfunction. The data were analyzed by descriptive statistics and adjusted odds ratios with their 95% CIs. Results: According to the results, around 58% of men were found to suffer from sexual dysfunction. The most prevalent type of sexual dysfunction was premature ejaculation, (34.7%), orgasm disorder (28.0%), desire sexual disorder (9.2%), delayed ejaculation (8.5%), retrograde ejaculation (6.8%) and erection dysfunction (5.5%). The men with a history of primary infertility had 3.61 fold risk of sexual dysfunction compared to women who had secondary infertility. Male Infertility (odds ratio, 3.61 95% CI, 2.13-4.58) and idiopathic were (odds ratio, 3.43 1.23-4.85) factors significantly associated with sexual dysfunction. There was 4.92 fold risk of sexual dysfunction observed in men whose wives had sexual dysfunction as compared with those whose wives had no sexual dysfunction. Conclusion: This study shows a high prevalence of sexual dysfunction for male partners of infertile couples in a community in Babol, Iran. It would be beneficial to establish a sexual clinic in infertility centers for the professional staff to monitor infertile couples.